Tito and his partisans : what really happened in Yugoslavia from 1941 to 1945 - Kapetanovic, Nikola (Belgrade : Jugoslovenska Knjiga)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Wereldoorlog 2; Joegoslavië